2004
DOI: 10.1191/0269216304pm902oa
|View full text |Cite
|
Sign up to set email alerts
|

A study into the educational needs of children's hospice doctors: a descriptive quantitative and qualitative survey

Abstract: There is a disparity between educational needs as derived from self-rated competencies and from educational diary keeping; suggesting that children's hospice doctors may not be fully aware of their own educational, support and training needs. Self-rated competencies emphasise the value of education in craft or clinical skills; whereas personal diary keeping emphasises the value of education in intrapersonal and interpersonal skills such as communication, team-working and personal coping skills. The current cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…This finding is consistent with prior studies showing weak or absent associations between clinician self-assessments and external evaluations in fields of pediatric hospice care, 16 ICU care, 17 prevention-oriented counseling, 18 and end-of-life care practices, 19 though none of these prior studies used patient or family assessments as external measurements. Our results are also consistent with a 2006 systematic review of physician self-assessment studies that found physicians to have limited ability to accurately selfassess their clinical skills.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with prior studies showing weak or absent associations between clinician self-assessments and external evaluations in fields of pediatric hospice care, 16 ICU care, 17 prevention-oriented counseling, 18 and end-of-life care practices, 19 though none of these prior studies used patient or family assessments as external measurements. Our results are also consistent with a 2006 systematic review of physician self-assessment studies that found physicians to have limited ability to accurately selfassess their clinical skills.…”
Section: Discussionsupporting
confidence: 89%
“…Amery and Lapwood6 studied the educational needs of children's hospice doctors through a descriptive quantitative and qualitative survey in which 35 paediatric hospice physicians answered a questionnaire designed to survey their self-assessed educational competencies in 19 subject areas. In a second stage, they prospectively recorded challenging cases and identified the physician's unmet educational needs.…”
Section: Introductionmentioning
confidence: 99%
“…2 The online questionnaire was derived from the International Children's Palliative Care Network (ICPCN) CPC curriculum (available by request to the author) and has been used by the author in previous studies that explore the educational needs of CPC health professionals in the UK, Uganda, Tanzania, and South Africa. 3,4 What we do know about CPC is that nearly all child deaths occur in resource-poor countries, almost half of them in Africa, where 1 in 8 children do not reach 5 years old 5 and where HIV/ AIDS and cancer are the two commonest incurable childhood diseases. 6 However, we do not know which types of organizations or professionals might be providing CPC, particularly in developing countries; nor do we know what the educational needs of those professionals might be.…”
Section: Introductionmentioning
confidence: 99%